Improving Students' Arabic Vocabulary Memorizing with Cognitive Retroactive Transfer (CRT) - Fira Eka Permatasari; Lailatul Mauludiyah (Arabic Education Program IAIN Pekalongan, 2022)
Learning Arabic vocabulary often brings difficulties, especially in memorizing and remembering vocabulary. Interesting learning methods can be a solution to these problems. This study aims to describe the application of the Cognitive Retroactive Transfer (CRT) method in Arabic vocabulary learning, focusing on honing students' cognitive abilities and memory so that they can easily remember and memorize the vocabulary they have learned. This study uses a pre-experimental design research approach with a one-group pretest-posttest and saturated sampling with a sample of 30 students. The data analysis technique used is the normality test to find out if the data that is distributed is normally distributed. Furthermore, the researchers used the Paired Sample T-Test and Effectiveness Test to determine the effectiveness of the applied method. The Cognitive Retroactive Transfer (CRT) method is applied by giving a test which is then assessed directly by the teacher. The teacher provides an evaluation and the test is applied directly by the students in everyday life. With this method, students are expected to be able to remember and memorize the Arabic vocabulary they have learned. The trial application of the Cognitive Retroactive Transfer (CRT) method reaped positive results where approximately 70% of class IX students at SMP Muhammadiyah 1 Malang City were able to remember and apply the vocabulary they had learned when communicating in daily life.